PELATIHAN MOTIF BATIK JUMPUTAN MELALUI TEKNIK PERCAMPURAN WARNA KHAS BETAWI DIDESA SUKAMUKTI - Kiah, Delia Aminah; Sundari, Kori; Rikmasari, Rima (An-Nizam, 2024)
Making jumputan with basic fabrics, will be very helpful in efforts to produce quality jumputan fabric products, so that it will improve the welfare of the local community, The implementation of this practical activity is carried out offline / face-to-face, at the Darut Tawwabin foundation, Sukamukti Village, with the aim of improving the skills of teenagers to be more honed and to produce quality products and can be traded. Being able to develop skills and see the extent of the youth's batik knowledge, making jumputan batik on the basis of cloth, will be very helpful in efforts to produce quality jumputan cloth products, so that it will improve the welfare of the community and the economy of the local community. The results of this service activity show that the teenagers of Sukamukti Village can develop batik skills and see the talents they have, thus making business fields and helping the local economy.